(untitled) (Journal of Philosophy Culture and Political Science, 2015)
This article dedicated to the analyses of theoretical and methodological bases of international negotiation. World outlook and methodological bases of international negotiation consists the complex of philosophic and general theoretical ideas about negotiation. Ideas of politics accumulates in the analyses, approaches and orientations of international political cognition. In modern international negotiation exists various methodological concepts of analyses of international negotiation process. One of the branches of aforementioned science are theoretical and methodological basis which helps to form international negotiations as a study or subject and methods of searching which view international negotiations as a goal of science. This article says about the important and urgent role of international negotiations in the field of world politics. The methodology of international negotiations consists of several stages of formation. Thoughts and hypotheses of scholars concerning the theoretical and methodological basis of international negotiations are significant. Methods of understanding of American, European and Russian scholars helped to find out political reality through the international negotiations.